Prenatal diagnosis of anomalous drainage of the right superior vena cava to the left atrium - Killen, Stacy (Prenatal Cardiology, 2022)
Anomalous drainage of the right superior vena cava to the left atrium, as an isolated abnormality, is a very rare form of congenital heart disease that causes postnatal hypoxemia. There is only one other case reported in the literature of this anomaly diagnosed prenatally. We describe a case of isolated right superior vena cava to the left atrium diagnosed prenatally by our fetal cardiology team after obstetrical referral for a dilated superior vena cava, and we discuss the differential diagnosis of in utero dilation of the superior vena cava.